1997
DOI: 10.1111/j.1439-0418.1997.tb01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to native host abandonment by the coffee berry borer Hypothenemus hampei (Ferr.) (Col., Scolytidae)

Abstract: The coffee berry borer (CBB) Hj'pothenemus hanipei is a serious pest of coffee berries. The 'interseason' is the most critical period for this beetle because at this time the vast majority of remaining berries or new immature berries are unsuitable for the development of this pest. CBB abandons its native berry to search for another host berry. This work shows that some factors affect the abandonment of female and specifies some biological characteristics of the particular female of the interseason. The follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 2 publications
(1 reference statement)
3
58
0
11
Order By: Relevance
“…Mortality in ground berries was much higher than that found in a similar experiment under dry season conditions in Mexico (Baker et al, 1992a). Penados and Ochoa (1977) and Mathieu et al (1997) have demonstrated that females may delay oviposition as a mechanism of adaptation under unfavorable conditions. Klein-Koch et al (1988) found that in a high rainfall zone of Ecuador (3300 mm year -1 ) more than 80% of bored berries fallen to the ground were rotted and with a very low population of borers; ripe and overripe berries were the most affected.…”
Section: Resultsmentioning
confidence: 71%
“…Mortality in ground berries was much higher than that found in a similar experiment under dry season conditions in Mexico (Baker et al, 1992a). Penados and Ochoa (1977) and Mathieu et al (1997) have demonstrated that females may delay oviposition as a mechanism of adaptation under unfavorable conditions. Klein-Koch et al (1988) found that in a high rainfall zone of Ecuador (3300 mm year -1 ) more than 80% of bored berries fallen to the ground were rotted and with a very low population of borers; ripe and overripe berries were the most affected.…”
Section: Resultsmentioning
confidence: 71%
“…Tal preferência foi demonstrada em estudos em laboratório e no campo (MENDONZA-MORA, 1991;GIORDANENGO;FRÉROT, 1993;MATHIEU et al, 1997b;MATHIEU et al, 1991). Todavia, os resultados de estudos envolvendo a seleção de cores por fêmeas da broca-do-café são conflitantes, reforçando a hipótese de que vários fatores, além da cor, estão envolvidos no processo de localização e colonização de frutos de café por fêmeas de H. hampei (MENDONZA-MORA, 1991;FRÉROT, 1997a).…”
Section: Estímulos Visuaisunclassified
“…O comportamento de abandono do fruto é estimulado por diversos fatores, tais como: olfativos, ou seja, resposta aos voláteis emitidos por frutos de café; intensidade luminosa; umidade relativa do ar; cor do fruto; e estado fisiológico da fêmea (MATHIEU; BRUN; FRÉROT, 1997, MATHIEU et al, 2001). …”
Section: Comportamento De Abandono Do Fruto Nativounclassified
“…Contudo, os machos nunca exibem esse comportamento (MATHIEU; BRUN; FRÉROT, 1997). Posteriormente, o processo de colonização irá depender das condições internas do fruto (DAMON, 2000, ORTIZ et al, 2004.…”
Section: Comportamento De Abandono Do Fruto Nativounclassified
See 1 more Smart Citation